Analysis of the Presence and Risk Factors of Bacteria Escherichia Coli In Orange JuiceIn Takengon 2023 - Ihktiara Maghirah S (SEAN Institute, 2024)
Oranges are one of the fruits that are easily obtained and have many health benefits. Oranges are generally consumed in the form of juice. Fresh fruit juices that are widely consumed by the public are usually made from a mixture of fresh fruit, ice, sugar, or milk without any heating process in their processing, causing fruit juice to be at high risk of being contaminated with E. coli. The presence of E. coli in water or food is also considered to have a high correlation with the discovery of germs in food. The purpose of this study was to determine whether orange juice was contaminated with Escherichia coli bacteria.. This type of research uses a qualitative method where data collection is carried out by interview. The results of the study, based on the results of the examination from the Laboratory that out of 10 juice samples, there were 3 samples containing Escherichia coli bacteria, namely in sample codes k3, k7 and k9. Contamination is likely to occur due to less clean handlers and using uncooked mixing water. The presence of Escherichia coli bacteria in drinks or food is also considered to have a high correlation in the discovery of food pathogens.